Trauma, Experience and Narrative in Europe after World War II
XV, 337 p. 4 illus.
Keywords: This book promotes a historically and culturally sensitive understanding of trauma during and after World War II. Focusing especially on Eastern and Central Europe, its contributors take a fresh look at the experiences of violence and loss in 1939–45 and their long-term effects in different cultures and societies. The chapters analyze traumatic experiences among soldiers and civilians alike and expand the study of traumatic violence beyond psychiatric discourses and treatments. While acknowledging the problems of applying a present-day medical concept to the past, this book makes a case for a cultural, social and historical study of trauma. Moving the focus of historical trauma studies from World War I to World War II and from Western Europe to the east, it breaks new ground and helps to explain the troublesome politics of memory and trauma in post-1945 Europe all the way to the present day. This book is an outcome of a workshop project ‘Historical Trauma Studies,’ funded by the Joint Committee for the Nordic Research Councils in the Humanities and Social Sciences (NOS-HS) in 2018–20. Chapters 4, 5 and 6 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Ville Kivimäki is Senior Research Fellow at Tampere University, Finland. He leads the Lived Nation research team at the Academy of Finland’s Centre of Excellence in the History of Experiences (HEX). Peter Leese is Associate Professor of Social and Cultural History at the Institute of English, Germanic and Romance Studies, University of Copenhagen, Denmark.